Efficacy of raltegravir-containing regimens in antiretroviral-naïve and -experienced individuals in routine clinical practice. (November 2016) - Jaeckle, M; Khaykin, P; Haberl, A; De Leuw, P; Schüttfort, G; Stephan, C; Wolf, T
Summary: Raltegravir is one of the standard antiretroviral therapy (ART) options in treatment-experienced and -naïve patients. However, efficacy data from clinical practice are scarce. Therefore, the efficacy of raltegravir-containing ART in clinical practice was investigated retrospectively. In all, 295 treatment-naïve and -experienced patients were analysed using two different cut-offs for virological failure (200 or 50 copies/ml). The response at week 24 and onwards was evaluated as a 'time to loss of virological response' analysis and estimated as a survival function. Additionally, dual therapy regimens (raltegravir plus boosted protease inhibitor) were compared to standard combinations in experienced patients performing a snapshot analysis at weeks 24 and 48, as well as a time to loss of virological response analysis. A total of 86.2% of the 64 treatment-naïve patients maintained virological suppression using a cut-off of 200 copies/ml (c/ml), while 67.7% maintained virological suppression with a 50 copies/ml cut-off from week 24 until the end of observation. Among the 231 treatment-experienced patients, 84.8% maintained virological suppression from week 24 onwards using a cut-off of 200 copies/ml; and 71.0% using 50 copies/ml, respectively. In the subgroup snapshot analysis at week 24, 98.3% (86.7% using a cut-off of 50 copies/ml) and at week 48, 93.3% (80.0%) of patients responded to dual therapy. Patients who were receiving a standard background therapy responded in 88.3% (81.3%) at week 24 and in 86.0% (80.7%) at week 48. Differences were not significant. This study shows again the overall long-term efficacy of raltegravir-based ART and furthermore gives reference for a comparable efficacy of dual and standard nucleos(t)ide reverse transcriptase inhibitor–backbone regimens in experienced patients on raltegravir over a period of 48 weeks in a real-life cohort where patients with severe comorbidities were included.